Notes on nomenclature of Sycetta Haeckel, 1872 and reinstating the family Syconidae Poléjaeff, 1883 (Calcarea, Porifera) - Sanamyan, K.; Sanamyan, N. (Zootaxa, 2021)
In the present paper we describe nomenclatural history of several genera and families of Calcarea (in chronological order) and then discuss nomenclatural consequences which stem from previous incorrect fixation of the type species of the genus Sycetta Haeckel, 1872.